Decompressive Hemicraniectomy in a South American Population - Morbidity and Outcomes Analysis - Vital, Roberto Bezerra [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP]; Luvizutto, Gustavo Jose [UNESP]; Ducati, Luis Gustavo [UNESP]; Braga, Gabriel Pereira [UNESP]; Carvalho Nunes, Helio Rubens de [UNESP]; Romero, Flavio Ramalho [UNESP]; Ganem, Eliana Marisa [UNESP]; Zanini, Marco Antonio [UNESP]; Bazan, Rodrigo [UNESP] (Public Library Science, 2016)
Background Malignant cerebral artery strokes have a poor prognosis, with nearly 80% of mortality in some series despite intensive care. After a large randomized trial, decompressive hemicraniectomy has been performed more often in stroke patients. Here, we describe patients in a tertiary teaching hospital in Brazil, emphasizing the impact of age on outcomes. Methods A retrospective cohort of patients, with malignant strokes which received a decompressive hemicraniectomy, from paper and electronic medical records, from January 2010 to December 2013 was divided into two groups according to age. Results The final analysis included 60 patients. The overall mortality was higher among patients older than 60 yrs (67% vs. 41%; p = 0.039), whose group also had a worse outcome (76% with mRS 5 or 6) at 90 days (OR 3.91 CI95% 1.30-11.74), whereas only 24% had mRS of 0-4 (p = 0.015). All patients who presented with sepsis died (p = 0.003). The incidence of pulmonary infection was very high in the elderly group (76%) with significant intergroup differences (p = 0.027, OR 8.32 CI95% 0.70-98.48). Conclusions Older patients present more commonly with infections, more disabilities and a higher mortality, highlighting very poor results in elderly population. These results should be proved with a South American trial, and if confirmed, it can impact on future decisions regarding decompressive craniectomy for acute ischemic stroke in our region.